2009
DOI: 10.1007/s00432-009-0742-x
|View full text |Cite
|
Sign up to set email alerts
|

MnSOD Val16Ala polymorphism and prostate cancer susceptibility: a meta-analysis involving 8,962 Subjects

Abstract: This meta-analysis suggests that the Ala allele of the MnSOD gene was a low-penetrance susceptible gene in PCA development, especially in Caucasians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…high Gleason sum) tumors, likely differ from risk factors for total incident prostate cancer (12). In addition, several single nucleotide polymorphisms (SNPs) in antioxidant genes have been associated with prostate cancer, and these may modify the relations between circulating or dietary antioxidants and prostate cancer (13, 14). Thus, the discrepant results for antioxidants and prostate cancer may be due to a lack of focus on clinically relevant, advanced forms of the disease or the inability to account for the impact of genetic variants on antioxidant metabolism and availability.…”
Section: Introductionmentioning
confidence: 99%
“…high Gleason sum) tumors, likely differ from risk factors for total incident prostate cancer (12). In addition, several single nucleotide polymorphisms (SNPs) in antioxidant genes have been associated with prostate cancer, and these may modify the relations between circulating or dietary antioxidants and prostate cancer (13, 14). Thus, the discrepant results for antioxidants and prostate cancer may be due to a lack of focus on clinically relevant, advanced forms of the disease or the inability to account for the impact of genetic variants on antioxidant metabolism and availability.…”
Section: Introductionmentioning
confidence: 99%
“…But, the role of OS and polymorphisms of the antioxidant enzymes on carcinogenetic process has been studied extensively in recent years. [7][8][9][10] The L55M and Q192R functional polymorphisms are the two most common examples of PON1 polymorphism in the human serum that have been studied in the previous studies related with the cancer and polymorphisms. Two important mutations in 55 and 192 codons of PON1 which affect paraoxonase activities have been shown in molecular studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that SNPs contribute to interindividual variability in susceptibility to common diseases such as cancer [35,36]. So far, some published meta-analyses have confirmed that a number of SNPs are associated with increased or decreased PCa risk in different races, such as A49T in steroid-5-alpha-reductase, alpha polypeptide 2 (SRD5A2) gene [37], Gly388Arg in fibroblast growth factor receptor 4 (FGFR4) gene [38], -160C/A in E-cadherin (CDH1) gene [39], Val16Ala in manganese superoxide dismutase (MnSOD) gene [40], C677T in 5,10-methylenetetrahydrofolate reductase (MTHFR) gene [41]. Several studies have investigated the possible role of anti-tumor gene polymorphisms and the prevalence of PCa.…”
Section: Discussionmentioning
confidence: 99%